1990
DOI: 10.1007/bf00035010
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of photosystem II heterogeneity in Dunaliella salina (green algae)

Abstract: Based on the electron-transport properties on the reducing side of the reaction center, photosystem II (PS II) in green plants and algae occurs in two distinct forms. Centers with efficient electron-transport from QA to plastoquinone (QB-reducing) account for 75% of the total PS II in the thylakoid membrane. Centers that are photochemically competent but unable to transfer electrons from QA to QB (QB-nonreducing) account for the remaining 25% of total PS II and do not participate in plastoquinone reduction. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…This process is accelerated, and recovery is completely prevented, by CAP, an inhibitor of chloroplast protein synthesis. We suspect that this process may reflect photoinhibitory damage to PSII involving loss of PSII functions, perhaps based on the dynamics of the D1 polypeptide of the reaction center, as has been explored in other studies (Chow et al 1989;Aro et al 1990;Guenther and Melis 1990;Richter et al 1990;Ohad et al 1990).…”
Section: Discussionmentioning
confidence: 94%
“…This process is accelerated, and recovery is completely prevented, by CAP, an inhibitor of chloroplast protein synthesis. We suspect that this process may reflect photoinhibitory damage to PSII involving loss of PSII functions, perhaps based on the dynamics of the D1 polypeptide of the reaction center, as has been explored in other studies (Chow et al 1989;Aro et al 1990;Guenther and Melis 1990;Richter et al 1990;Ohad et al 1990).…”
Section: Discussionmentioning
confidence: 94%
“…However, a remarkable feature of plant and algal chloroplasts, as well as cyanobacteria, is their ability to adjust their photosynthetic apparatus in relation to available irradiance. Short-term acclimation is achieved through so-called transitions from State I to State II whereby electron transport through the two photosystems can be adjusted in relation to light quality and\or the relative demands for ATP and NADPH (Manodori & Melis, 1984 ;Allen et al, 1989 ;Guenther & Melis, 1990). Longer-term acclimation involves regulation of the relative abundances of the various proteins of the photosynthetic apparatus in relation to irradiance during growth.…”
Section: Light and Nitrogen Relationsmentioning
confidence: 99%
“…In recent work it was shown that light plays a role in modulating the pool size of the QBnonreducing centers (Guenther and Melis 1989b).…”
Section: Measurements With Intact Cellsmentioning
confidence: 99%
“…In recent work the question of the pool size and pool dynamics of PS II QB-nonreducing centers in D. salina was addressed (Guenther and Melis 1989b). It was found that the pool size of QBnonreducing centers was maintained at a steadystate level under continuous illumination.…”
Section: Introductionmentioning
confidence: 99%